Digital Literacy: Creating a Friendly Space for Communication for the Elderly At LII (Indonesia Elderly Institution), Makassar - Anwar, Citra Rosalyn; Kanata, Arnidah; Ohan, Faridah (UPT Publikasi Ilmiah UNISBA, 2025)
As the communication space and public services shift to the digital world, elderly need to be able to use digital devices safely and comfortably. Elderly, as users of digital platforms, require special attention, mainly due to the widespread dissemination of online information. Assistance for older people is crucial so that they can communicate and interact comfortably in the digital world. One of these efforts is realised through the Elderly Digital Academy program from Tular Nalar, which was then developed by the Indonesian Elderly Institute (LLI) in Makassar as a mentoring and training program. This study assisted 32 elderly individuals in addressing issues such as hoaxes, online fraud, and digital transactions. The goal is to empower elderly to become active internet users who can create and disseminate fact- based educational content. Although the elderly face challenges such as fake news and hate speech, they still have the spirit to learn and contribute. Digital literacy for elderly is not just about disseminating information, but also creating collaborative spaces and encouraging active participation in digital communities.